Empagliflozin improves outcomes in patients with heart failure and preserved ejection fraction irrespective of age - Böhm, Michael; Butler, Javed; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Abdin, Amr; Mahfoud, Felix; Brückmann, Martina; Gollop, Nicholas D.; Iwata, Tomoko; Ponikowski, Piotr; Wanner, Christoph; et al. (Journal of the American College of Cardiology, 2022)
Background - Empagliflozin reduces cardiovascular death (CVD) or heart failure (HF) hospitalization (HFH) in patients with HF and preserved ejection fraction. Treatment effects and safety in relation to age have not been studied. - Objectives - The purpose of this study was to evaluate the interplay of age and empagliflozin effects in EMPEROR-Preserved (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Preserved Ejection Fraction). - Methods - We grouped patients (n = 5,988) according to their baseline age (<65 years [n = 1,199], 65-74 years [n = 2,214], 75-79 years [n = 1,276], ≥80 years [n = 1,299]). We explored the influence of age on empagliflozin effects on CVD or HFH (primary outcome), total HFH, rate of decline in estimated glomerular filtration rate, health-related quality of life with the Kansas City Cardiomyopathy Questionnaire-Clinical Summary Score, and frequency of adverse events. - Results - Considering only patients on placebo, the incidence of primary outcomes (P trend = 0.02) and CVD (P trend = 0.003) increased with age. Empagliflozin reduced primary outcomes (P trend = 0.33), first HFH (P trend = 0.22), and first and recurrent HFH (P trend = 0.11) across all age groups with an effect being similar at ≥75 years (P interaction = 0.22) or >80 years (P interaction = 0.51). Empagliflozin improved Kansas City Cardiomyopathy Questionnaire-Clinical Summary Score at week 52 and attenuated the decline of estimated glomerular filtration rate without age interaction (P = 0.48 and P = 0.32, respectively). There were no clinically relevant differences in adverse events between empagliflozin and placebo across the age groups. - Conclusions - Empagliflozin reduced primary outcomes and first and recurrent HFH and improved symptoms across a broad age spectrum. High age was not associated with reduced efficacy or meaningful intolerability. (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Preserved Ejection Fraction [EMPEROR-Preserved]; NCT0305951)